Open space for people: an overview of open space typologies and utilization in Kuala Lumpur - Abdul Majid, Noor Hanita; Sapian, Abdul Razak; Mohyuddin, Amira (2005)
This paper presents an overview on the typologies of open spaces in Kuala Lumpur. The typologies of open spaces discussed include parks, squares, plazas, street and waterfronts. Classifying the open spaces by purpose, usage and location develops by typologies. Results presented will cover the utilization patterns of various open space typologies. The design factors of the open spaces will be discussed in terms of the key qualities, amenities and landscape elements provided. This research recorded these factors, which are deemed to be strongly related to utilization rate of the open spaces. The analysis on the data collected indicated that the open spaces are mainly utilized for recreation, meeting places and other social activities. These open spaces proved to be a relief system that supported the quality of life in cities. In order to assess the stressfulness of the open spaces, the amenities provided are correlated to the satisfaction votes by the users/ respondents. The open spaces are also assessed in terms of thermal comfort responses from the users. The thermal comfort votes are analyzed through cross tabulation to the activities conducted at the open spaces. The results indicated that the open spaces in Kuala Lumpur city are utilized for many different activities according to the typologies. The thermal comfort votes also suggested that the open spaces are thermally acceptable to the users.